Analysis of Commuting Time and Health Impact in Jakarta Metropolitan Area: A Comparative Review - Michael Michael; Khrisna Pramudya Tectona Malau; Daru Seto Bagus Anugrah; Deka Prismawan (Jurnal Perkotaan, 2025)
Commuting in the Jakarta Metropolitan Area (Jabodetabek) presents significant challenges, including long travel times, congestion, and environmental concerns, which affect commuters' health and well-being. This study provides a comparative review of commuting patterns, transportation modes, and their associated health impacts. By analyzing secondary data, the research identifies key issues such as the prevalence of private vehicle use, overcrowded public transport, and limited infrastructure for sustainable travel. The findings reveal that prolonged commutes are linked to physical inactivity, musculoskeletal problems, respiratory conditions, and mental stress, exacerbated by inadequate transportation systems and environmental factors. Comparisons with other global cities underscore the importance of integrated transit networks, sustainable transport policies, and urban planning to mitigate these impacts. This review aims to inform policy decisions to enhance the quality of life for Jakarta’s commuters and foster a more sustainable urban future.